Spirituality moderates hopelessness and suicidal ideation amongst Iranian depressed adolescents - Abdollahi, Abbas; Abu Talib, Mansor (Routledge, 2015)
To examine the moderating role of spirituality between hopelessness, spirituality, and suicidal ideation, 202 Iranian depressed adolescent inpatients completed measures of patient health, suicidal ideation, hopelessness, and core spiritual experience. Structural equation modelling indicated that depressed inpatients high in hopelessness, but also high in spirituality, had less suicidal ideation than others. These findings reinforce the importance of spirituality as a protective factor against hopelessness and suicidal ideation.